The efficacy and safety in radioactive iodine refractory thyroid cancer patients treated with sorafenib - Ling, Yuanna; Xiong, Xiaoli; Luo, Jiaxin; Zou, Quanliang; Chen, Pan; Pan, Liqin; Long, Man; Feng, Huijuan; Ouyang, Wei (Frontiers in Endocrinology, 2023)
Background Sorafenib included in Chinese medical insurance is the earliest targeted drug for radioactive iodine refractory differentiated thyroid cancer (RR-DTC). This study is to further demonstrate the clinical efficacy and safety of sorafenib used in Zhujiang Hospital of Southern Medical University. Methods RR-DTC patients treated at our Department of Nuclear Medicine in Zhujiang Hospital of Southern Medical University (October 2017–May 2020) were retrospectively analyzed. Treatment effects, progression-free survival (PFS), and adverse effects (AEs) during medication were evaluated. Results Of the 31 patients included, 26 patients were evaluated for efficacy with a median follow-up time of 17.5 months (4.0–51.0 months). The disease control rate (DCR) was 57.7% (n = 15) and the objective response rate (ORR) was 26.9% (n = 7). Most patients with disease control had thyroglobulin decreases of more than 60% (p = 0.004), ORRs were favorable in patients with lung metastasis and lung-only metastasis (p = 0.010 and 0.001, respectively). The PFS of the 26 patients analyzed was 16.5 months (95%CI: 14.41 –23.90 months). In the subgroup analysis, female, patients with lung-only metastasis, hand-foot skin syndrome (HFS), and thyroglobulin response ≥ 60% observed longer PFS (p = 0.038, 0.045, 0.035, and 0.000, respectively), while patients with bone metastasis had lower PFS (p = 0.035). The most common toxicity profile was HFS (93.5%), followed by diarrhea (83.9%), alopecia (74.2%). All the side effects were mainly grade 1–2. Grade 3–4 adverse reactions were more common in diarrhea and HFS. Conclusions Sorafenib has promising efficacy in RR-DTC, especially in patients with lung metastasis and lung-only metastasis. The AEs of sorafenib were generally mild, and the main AE was HFS.